Effects of temporary calf removal and eCG on pregnancy rates to timed-insemination in progesterone-treated postpartum Nellore cows - Pinheiro, V. G. [UNESP]; Souza, A. F. [UNESP]; Pegorer, M. F. [UNESP]; Satrapa, R. A. [UNESP]; Ereno, Ronaldo Luiz [UNESP]; Trinca, L. A. [UNESP]; Barros, C. M. [UNESP] (Elsevier B.V., 2009)
The objective was to evaluate the effects of temporary calf removal (TCR), eCG administration, or both, in a progesterone-based protocol. Suckled Nellore cows (40-80 d postpartum, n = 443) with body condition scores from 2.0 to 3.5 (5-point scale) on three farms were all given a synchronizing protocol (PEPE). At the start (designated Day 0), cows were given an intravaginal device (1.0 g of progesterone) and 2.5 mg of estradiol benzoate (EB) im. on Day 8, the device was removed and cows were given PGF(2 alpha) (150 mu g of D-cloprostenol im), followed in 24 h by 1.0 mg EB im, and 30-36 h thereafter, fixed-time AI. The design was a 2 x 2 factorial; main effects were TCR (54-60 h; from device removal to FTAI) and eCG treatment (300 IU im, concurrent with PGF(2 alpha)). Transrectal ultrasonography was done on Days - 10 and 0 to detect anestrus (absence of a CL at both examinations) and similar to 30 d after FTAI (pregnancy diagnosis). Data were analyzed by logistic regression. The following variables did not significantly affect pregnancy rates: farm, postpartum interval, cyclicity, inseminators, and semen (sire). Overall, 77% of the cows were deemed anestrus. Pregnancy rates were similar (P > 0.05) among treatment groups: Control (54/108 = 50.0%), TCR (44/106 = 41.5%), eCG (63/116 = 54.3%), and TCR + eCG (49/113 = 43.4%). Pregnancy rate was higher in multiparous than primiparous cows (186/360, 51.7% vs. 24/83,28.9%, P < 0.01), but was not significantly affected by cyclicity status or body condition score. In conclusion, temporary calf removal, eCG, or both, did not significantly increase pregnancy rate to timed-insemination in a progesterone-based synchronization protocol in postpartum Nellore cows with acceptable body condition. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Fixed-time artificial insemination; Progesterone; Bovine; eCG; Temporary calf removal